Development of Tailor-Made Dendrimer Ternary Complexes for Drug/Gene Co-Delivery in Cancer - Ana Raquel Neves; Tânia Albuquerque; Rúben Faria; Milan Paul; Swati Biswas; Ângela Sousa; Diana Costa (MDPI AG, 2021)
Cancer gene therapy, mediated by non-viral systems, remains a major research focus. To contribute to this field, in this work we reported on the development of dendrimer drug/gene ternary complexes. This innovative approach explored the great capacity of both polyamidoamine (PAMAM)-paclitaxel (PTX) conjugate and polyethylenimine (PEI) polymers to complex a p53-encoding plasmid DNA (pDNA), highlighting the utility of considering two compacting agents. The pDNA complexation capacity has been investigated as function of the nitrogen to phosphate groups ratio (N/P), which revealed to be a tailoring parameter. The physicochemical properties of the conceived ternary complexes were revealed and were found to be promising for cellular transfection. Furthermore, the formulated co-delivery systems demonstrated to be biocompatible. The ternary systems were able of cellular internalization and payload intracellular release. Confocal microscopy studies showed the co-localization of stained pDNA with the nucleus of cancer cells, after transfection mediated by these carriers. From this achievement, p53 gene expression occurred with the production of protein. Moreover, the activation of caspase-3 indicated apoptosis of cancer cells. This work represents a great progress on the design of dendrimer drug/gene co-delivery systems towards a more efficient cancer therapy. In this way, it instigates further in vitro studies concerning the evaluation of their therapeutic potential, expectedly supported by the synergistic effect, in tumoral cells.